Numerical investigation on the mechanical response of steel-frame polyethylene pipelines subjected to strike-slip faulting - ZhaoLiang Zhu; Xin Huang (PLoS ONE, 2026)
This study investigates the failure behavior of buried steel-reinforced polyethylene (SRPE) pipelines crossing strike-slip faults. A high-fidelity three-dimensional pipe-soil interaction model is established using the finite element method, and layered modeling with tie constraints is adopted to replicate the synergistic mechanical characteristics between the PE matrix and steel frame. The effects of pipe-fault intersection angle, steel wire diameter, and soil type on the mechanical response, buckling morphology, and critical strain of the pipeline are systematically examined, and the applicability of three design codes (CSA Z662-2023, GB 50470−2017, EN 13476−3) is quantitatively evaluated. The results show that SRPE pipelines exhibit a three-stage mechanical behavior under fault displacement: elastic bending at small displacement, plastic buckling propagation at moderate displacement, and sectional distortion with global instability at large displacement. The steel frame and PE matrix form an efficient synergistic mechanism featured by “matrix energy dissipation and frame load-bearing”, where failure initiates from plastic deformation of the PE matrix and further induces steel frame yielding and pipeline leakage. The pipe-fault angle dominates the loading pattern: tension is dominant at 30°, while transverse compression at 150° represents the most hazardous condition. The optimal wire diameter ranges from 2.0 to 2.5 mm ; loess provides the strongest constraint, whereas sand is the weakest. Conventional constant strain criteria neglect the angle effect and show obvious limitations in engineering practice. The findings provide significant theoretical support for the seismic design and safety assessment of SRPE pipelines crossing active fault zones.